Adjunctive Use of Lasers in Peri-Implant Mucositis and Peri-Implantitis Treatment: A Systematic Review - Marianna Chala; Eugenia Anagnostaki; Valina Mylona; Anastasios Chalas; Steven Parker; Edward Lynch (MDPI AG, 2020)
Background: The aim of this systematic review is to compare the effectiveness of lasers in the treatment of implant mucositis and peri-implantitis compared to conventional treatment (non-surgical or surgical: resective or regenerative). Methods: Sources of PubMed, Cochrane and Google Scholar search engines were used on articles published from 1997 to 2020 in English, with selected keyword criteria applied. Nine randomized controlled trials (RCTs) were selected. Results: All included studies were considered of "high quality" according to the quality assessment scale. The comparative assessment of the RCTs was done twice for each RCT based on the type of treatment and according to wavelength. There is strong scientific evidence that, regarding non-surgical treatment, adjunct laser application can provide better results only in the short term (three months). Regarding the surgical approach, the method of decontamination plays a subordinate role. All wavelengths/applications presented similar results. Conclusion: Within the limitations of this study, the adjunctive use of lasers in the treatment of peri-implant inflammation is effective for up to three months; there is no strong evidence regarding the long term benefit compared to conventional treatment.